Sjukfrånvaro – Aspekter på mätning, arbetsmarknadens betydelse och effekter av intervention - Goine, Hans (Socialmedicinsk tidskrift, 2007)
I artikeln sammanfattas en avhandling som lades fram vid Institutionen för Hälsovetenskap vid Mittuniversitetet i maj 2006. Avhandlingen är en sammanläggningsavhandling med fyra delstudier. Syftet med avhandlingen var att studera olika aspekter på sjukfrånvaro. Avhandlingen inleds med en studie om jämförelse av olika sätt att mäta sjukfrånvaro och avslutas med en fallstudie. I artikeln diskuteras sjukfrånvarons relation till arbetslöshet och andra välfärdsystem. The overarching aim of the thesis was to study various aspects of sickness absence in relation to measuring methods, the labour market and various welfare subsystems, and also the effects of intervention. The empirical material consists of four studies; one register study (measures of sick leave), one longitudinal (sick leave and unemployment), one cross sectional (cost of welfare programs) and one cohort study (case study intervention). The principal findings in Study I were that, in the measurement of sickness absence, the choice of measure has a bearing on the outcome: epidemiological measures afford a more extensive picture of sick leave in a population than administrative measures. Study II showed that unemployment among men was conversely related to long-term sick leave: when unemployment was high in certain occupational groups, their risk of long-term sick leave decreased. One of the main findings of Study III, which focused on regional differences in sickness absence, is that welfare subsystems appear to function like communicating vessels in some cases. The concluding case study, Study IV, focusing on the effects of intervention funded by the Swedish Working Life Fund, showed that input size had no significant influence on sickness absence. Key words: Sickness absence, sick leave, disability pension, unemployment, maintenance, work injury, measures, early retirement, intervention, workplace, absenteeism.